Di TK Al-Ikhlas Upaya Meningkatkan Kemampuan Motorik Halus Anak Usia 5-6 Tahun Melalui Metode Melipat Kertas (Origami) Tembung - Keysa Zalia Amanda; Fauziah Nasution; Ahmad Syukri Sitorus (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2024)
Measuring the fine motor skills of children aged 5-6 years before implementing the paper folding (origami) method at Al-Ikhlas Tembung Kindergarten, (2) Analyzing the implementation of learning using the storytelling method in the context of fine motor skills at Al-Ikhlas Tembung Kindergarten, and (3) Knowing the increase in fine motor skills of children aged 5-6 years after implementing the paper folding (origami) method at Al-Ikhlas Tembung Kindergarten. The method used in this research is Classroom Action Research (PTK) with a quantitative and qualitative approach. The research subjects consisted of 12 children aged 5-6 years, who were class A students at Al-Ikhlas Tembung Kindergarten, consisting of 8 boys and 4 girls. This research was carried out from May until completion, covering preparation and implementation activities. This research adopts the Kemmis and Mc design model. Taggart, implemented in two cycles, namely cycle I and cycle II. The results from cycle I showed a percentage value of 10.3%, while in cycle II it increased to 14.3%. The results of research from pre-action, cycle I, and cycle II show that the average child has improved. The increase in children's fine motor skills shows that the paper folding method (origami) is effective in improving the fine motor skills of children aged 5-6 years. Thus, the paper folding method (origami) can be considered as one method that can be used to improve the fine motor skills of children in this age range.